Analysis Of Microeconomic Theory According To Abu Ubayd And Al-Syaibani And Its Relevance To Pancasila Economy - Adil, Ustad; Janwari, Yadi; Jubaedah, Dedah (PT. Anagata Sembagi Education, 2024)
This study aims to analyze the microeconomic theory of Abu Ubayd in the book Al-Amwal and Al-Syaibani in the book al-Kasb and its relevance to the Pancasila economy. The research method used is a qualitative method with an analytical descriptive approach to the book of Al-Awal by Abu Ubayd and the book of Al-Kasb by Al-Syaibani and assisted from other reading sources related to the research title. Theresults of this study are Abu Ubayd in al-Amwal talks about basic human needs, legal and economic justice, Bedouin and urban dichotomy, while al-Syaibani explores the concept of al-Kasb (Work), according to him that work is the main element of production, has a very important position in life. Al-Syaibani also explained about wealth and destitution, the classification of businesses and about economic needs and specialization and distribution of work. The relevance of Abu Ubayd's economic thought with Pancasila Economy in accordance with the Indonesian Law No. 5 Year 1999 on the prohibition of monopolistic practices. While Al-Syaibani about al-Kasb (work) and the distribution of work is very relevant to the 1945 Constitution article 28 D Paragraph 2, namely Everyone has the right to work and get a fair and decent reward and treatment in labor relations.